Intensidade da coloração verde das folhas da grama esmeralda submetida a doses de nitrogênio e ao uso de herbicidas como reguladores de crescimento - Gazola, Raíssa Pereira Dinalli [UNESP]; Buzetti, Salatiér [UNESP]; De Niro Gazola, Rodolfo [UNESP]; De Castilho, Regina Maria Monteiro [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; De Souza Celestrino, Thiago [UNESP]; Dupas, Elisaˆngela [UNESP] (FapUNIFESP (SciELO), 2016)
Nitrogen (N) is the main nutrient responsible for the green coloration of lawns but also stimulates the growth of the aerial portion of grass, thus increasing mowing expenses. Therefore, herbicides may be used as a growth regulator. The ideal herbicide will reduce lawn height without affecting esthetics. Toward this end, the aim of the present study was to evaluate the green coloration of Emerald grass (Zoysia japonica Steud.) under the effect of different N doses or herbicides used as growth regulators. The study site consisted of randomized blocks containing 20 treatments arranged in a 5×4 factorial design with four treatment groups: four herbicides (glyphosate, imazaquin, imazethapyr, and metsulfuronmethyl, accounting for 200, 420, 80, and 140g ha-1 of the active ingredient, respectively) and the control sample (no herbicide); and three doses of N in the form of urea (5, 10, and 20g m-2), divided into five applications per year, in addition to a treatment without N. Leaf chlorophyll content (LCC) was assessed and the aerial portion of the lawn was measured with digital image analysis. Doses of N ranging from 10 to 20g m-2, divided into five applications a year, provided the lawn with intense green coloration, and the herbicides glyphosate (200g ha-1), imazaquin (420g ha-1), and imazethapyr (80g ha-1) were reported to be suitable for use as growth regulators of the study species, considering maintenance of esthetic quality (green coloration). The digital image analysis of the aerial portion provided more accurate results than use of a chlorophyll meter with regard to the recommendation of both N dose and herbicides to be used as growth regulators of Emerald grass.
Nitrogen dose and type of herbicide used for growth regulation on the green coloration intensity of Emerald grass
Keywords: Digital imaging; Fertilization; Glyphosate; Imazaquin; Imazethapyr; Lawn; Leaf chlorophyll content; Metsulfuron-methyl; Zoysia japonica steud